WOMEN IN AMERICAN FOOTBALL BEACH ON RIO DE JANEIRO (Fiep Bulletin - online, 2013)
The objectives of the study were to identify and analyze the difficulties and adherence of women in American Football in Rio de Janeiro. The participation of women in sports scenario was considered an insult and could render punishment. In contemporary times, the woman runs for public spaces varied, including the predominantly male. In the female American Football is no different; the woman has been entering and breaking paradigms that justify social roles on the basis of biological differences. This research will contribute both to the studies in physical education from the perspective of gender, problematized and reflecting on the sports recognized historically as viris and thus associated with the male, and to enable visibility to sports and women that practice. The population was composed of ten (10) female athletes who engage in the American Football on the beaches of Rio de Janeiro. Because it is a qualitative research, we chose to work with data collected from the Content Analysis (Bardin, 1977). It was concluded that women practitioners of American Football have difficulties relating to lack of incentives, sponsorship and the refusal by relatives and friends consider the sport violent. The grip was so focused on benefits earned by athletes through practice, especially on issues concerning socialization, health, pleasure and changes in behavior, as in questions concerning the expectations of success in the sport.
Keywords: Women; American Football; Adhesion